Porcelain powder, preparation method thereof and porcelain-forming composition
By combining the inorganic flame retardant powder with zinc borate, the porcelain powder is prepared and rapid porcelain formation is achieved in the polymer, the problem of high temperature and long time of porcelain formation in traditional ceramic powder is solved, and the flame retardant performance of polymer materials is significantly improved.
Patent Information
- Application Number
- CN202211730671.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The ceramic powders have high temperature and long time, making it difficult to quickly form porcelain in polymer materials, resulting in insufficient flame retardant performance.
Inorganic flame retardant powder is combined with zinc borate coated on its surface to prepare porcelain powder, and it can quickly form porcelain below 1000°C in polymer by specific preparation methods.
Rapid porcelain formation in polymer materials is achieved, the oxygen index and flame retardant properties are improved, and the porcelain formation temperature and time are reduced.
Smart Images

Figure CN116003881B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of flame retardant materials, and in particular to a ceramic powder and a preparation method thereof and a ceramic composition. Background technology:
[0002] With the development of social science and technology and the improvement of living standards, organic polymer composite filling flame retardant materials have developed rapidly, and their output has increased year by year. Composite polymer materials have been widely used in building materials, decorative materials, wires and cables, electronic appliances, information and transportation.
[0003] Organic polymer composite filling flame retardant materials to achieve porcelain and flame retardant effects has developed into one of the new topics in flame retardant scientific research. In recent years, the market has attracted widespread attention to ceramic polymer composite materials in the field of passive fire protection. This material has the characteristics of low smoke, non-toxicity, and rapid transformation into ceramics under flame burning. It has very important economic significance, social benefits and theoretical research value for solving the fire resistance, flame retardancy and heat insulation problems of flame retardant polymers.
[0004] The surface temperature of the burning polymer material is 300-600℃, and strong thermal cracking occurs. When the polymer is heated to the thermal decomposition temperature, one or more of the following decomposition products are produced, such as combustible gases: methane, ethane, etc., such as non-combustible gases: carbon dioxide, water vapor, etc., such as liquids: usually partially decomposed plastics and high molecular weight organic compounds, such as solids: generally carbon-containing residues, such as charcoal or ash, such as solid particles and plastic fragments, which can form smoke. Obviously, when a fire is formed, the combustion process of polymer materials releases a large amount of smoke, which often causes great harm to the human body.
[0005] Therefore, it is necessary to develop a ceramic material that can quickly form ceramics when the polymer material burns, prevent the continuous cracking process of the polymer, form a shielding barrier layer, and achieve the effect of flame retardancy and smoke suppression. Summary of the invention:
[0006] The purpose of the present invention is to overcome the problems of high ceramic temperature and long ceramic forming time of traditional ceramic powders in the prior art, and to provide a ceramic powder and its preparation method and a ceramic composition. The ceramic powder can be quickly ceramicized in a polymer at below 1000°C, thereby improving the oxygen index and flame retardant properties of the polymer material.
[0007] In order to achieve the above-mentioned object, one of the objects of the present invention is to provide a ceramic-forming powder, comprising an inorganic flame-retardant powder and zinc borate coated on the surface of the inorganic flame-retardant powder.
[0008] A second object of the present invention is to provide a method for preparing a ceramic powder, the method comprising:
[0009] 1) dissolving a boron source in a first solvent to obtain a solution A;
[0010] dissolving a zinc source in a second solvent to obtain a solution B;
[0011] dispersing an inorganic flame retardant in a third solvent to obtain a solution C;
[0012] 2) mixing the solution B and the solution C to obtain a mixed solution, and then adjusting the pH value of the mixed solution to obtain a mixed solution D;
[0013] 3) adding the solution A dropwise into the mixed solution D and stirring evenly to obtain a mixed solution E, and then heating the mixed solution E to a certain temperature and keeping it warm for a period of time to obtain the ceramic powder.
[0014] The third object of the present invention is to provide a ceramic powder prepared according to the above method.
[0015] A fourth object of the present invention is to provide a ceramic composition comprising a polymer resin and the aforementioned ceramic powder.
[0016] Through the above technical solution, the present invention has the following technical effects:
[0017] Compared with conventional ceramic polymers, the ceramic composition provided by the present invention has the advantages of short ceramic formation time and low ceramic formation temperature, can quickly ceramicize during combustion, and improves the flame retardant properties of polymer materials. Description of the drawings:
[0018] Figure 1 The SEM images of the ceramic powder prepared in Example 1 at different magnifications;
[0019] Figure 2 This is the SEM image of tricalcium phosphate powder in Comparative Example 2;
[0020] Figure 3 Optical photographs of the ceramic polymer prepared in Example 1 and the ceramic polymer prepared in Comparative Example 2 after ceramicization;
[0021] Figure 4 The cross-sectional view of the samples of the ceramicizable polymers prepared in Example 6 and Comparative Example 5 after calcination. Specific implementation method:
[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The porcelain-forming temperature mentioned in the present invention refers to the lowest porcelain-forming temperature of the porcelain-forming composition, that is, the porcelain-forming composition can be porcelain-formed under the condition of not lower than this temperature.
[0025] As mentioned above, the present invention provides a ceramic-forming powder, comprising an inorganic flame-retardant powder and zinc borate coated on the surface of the inorganic flame-retardant powder.
[0026] According to the present invention, if the particle size of the ceramic powder is too large, the surface of the ceramic polymer will crack after ceramicization; if the particle size of the ceramic powder is too small, the ceramic strength of the ceramic polymer will be low. Under preferred conditions, the particle size of the ceramic powder is 1-100 μm, more preferably 2-50 μm, and more preferably 5-30 μm.
[0027] According to the present invention, the mass ratio of the zinc borate to the inorganic flame retardant powder is (10-40):100, for example, it can be 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100 or any value in the range consisting of any two of the above values.
[0028] According to the present invention, preferably, the inorganic flame retardant powder is selected from at least one of phosphate, metal oxide and silicate; the phosphate includes but is not limited to aluminum phosphate, aluminum dihydrogen phosphate, tricalcium phosphate, hydroxy calcium phosphate, calcium hydrogen phosphate, magnesium phosphate, magnesium phosphate stone, magnesium phosphate hydrate and magnesium ammonium phosphate hydrate; the metal oxide includes but is not limited to at least one of antimony trioxide, zinc oxide, boron oxide, silicon oxide, aluminum oxide, magnesium oxide, calcium oxide, titanium oxide, zirconium oxide and molybdenum oxide; the silicate includes but is not limited to calcium silicate, magnesium silicate, aluminum silicate, talc, kaolinite, olivine and mica. Further preferably, when the inorganic flame retardant powder is phosphate and / or silicate, the combination of zinc borate and inorganic flame retardant powder can not only reduce the porcelain forming temperature of the porcelain powder, but also improve the porcelain forming strength; in the present invention, the inorganic flame retardant powder is selected from at least one of phosphate and silicate.
[0029] The present invention prepares the above-mentioned ceramic powder by coating zinc borate on the surface of the inorganic flame retardant powder. Under preferred conditions, the method for preparing the ceramic powder includes:
[0030] 1) dissolving a boron source in a first solvent to obtain a solution A;
[0031] dissolving a zinc source in a second solvent to obtain a solution B;
[0032] dispersing an inorganic flame retardant in a third solvent to obtain a solution C;
[0033] 2) mixing the solution B and the solution C to obtain a mixed solution, and then adjusting the pH value of the mixed solution to obtain a mixed solution D;
[0034] 3) adding the solution A dropwise into the mixed solution D and stirring evenly to obtain a mixed solution E, and then heating the mixed solution E to a certain temperature and keeping it warm for a period of time to obtain the ceramic powder.
[0035] In the present invention, the content of zinc borate in the ceramic powder is adjusted by adjusting the dosage of the boron source, the zinc source and the flame retardant; under preferred conditions, the boron source is calculated as boron element, the zinc source is calculated as zinc element, and the mass ratio of the boron source, the zinc source and the inorganic flame retardant is (0.5-3):(0.5-3):(10-30).
[0036] According to the present invention, preferably, the inorganic flame retardant is selected from at least one of phosphates, metal oxides and silicates; preferably phosphates and / or silicates; further preferably at least one of phosphates and silicates, the phosphates including but not limited to aluminum phosphate, dihydrogen aluminum phosphate, tricalcium phosphate, hydroxy calcium phosphate, hydrogen calcium phosphate, magnesium phosphate, magnesium phosphate, magnesium phosphate hydrate, magnesium ammonium phosphate hydrate; the silicates including but not limited to calcium silicate, magnesium silicate, talc, kaolinite, olivine, mica; the metal oxides including but not limited to at least one of antimony trioxide, zinc oxide, boron oxide and molybdenum oxide.
[0037] In the present invention, the particle size of the ceramic powder is adjusted by adjusting the particle size of the inorganic flame retardant and the coating amount of the zinc borate. Under preferred conditions, the particle size of the inorganic flame retardant powder is 0.5-90μm, for example, it can be 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 30μm, 40μm, 50μm, 60μm, 80μm, 90μm or any value in the range composed of any two of the above values, more preferably 3-60μm, and more preferably 5-40μm.
[0038] According to the present invention, under preferred conditions, the boron source is a soluble boron source, including but not limited to borax, potassium borate and boric acid; the type of the zinc source may be known to those skilled in the art, including but not limited to at least one of zinc chloride, zinc nitrate and zinc sulfate; preferably, the first solvent, the second solvent and the third solvent are each independently selected from at least one of water and an organic solvent, and the organic solvent includes but is not limited to an alcohol solvent and a hydrocarbon solvent; in the present invention, the first solvent, the second solvent and the third solvent are all water.
[0039] According to the present invention, under preferred conditions, in step 2), the pH value of the mixed solution D is 7.5-10, for example, it can be 7.5, 8, 8.5, 9, 9.5, 10 or any value in the range consisting of any two of the above values.
[0040] According to the present invention, under preferred conditions, in step 3), the mixed solution E is kept at 90-150° C. for 6-10 hours.
[0041] In some preferred embodiments of the present invention, in step 3), the rate of dripping the solution A is 100-300 mL / 30 min.
[0042] In the present invention, step 3) also includes: washing, drying and grinding the product obtained by insulation; the washing, drying and grinding processes are all known to technicians in the relevant field, and the present invention will not be repeated here.
[0043] The present invention also provides a ceramic powder, which is prepared according to the above method.
[0044] The present invention also provides a ceramic composition, comprising a polymer resin and the ceramic powder mentioned above.
[0045] Preferably, based on the total amount of the polymer resin, the amount of the ceramic powder is 10-70wt%, for example, it can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 60wt%, 70wt% or any value in the range formed by any two of the above values; preferably 20-60wt%.
[0046] Preferably, the polymer resin includes at least one of polyolefin, polyolefin elastomer, polyphenylene ether resin, polyamide resin, polycarbonate, epoxy resin, polyurethane, acrylic resin, polyacrylonitrile resin, polyvinyl alcohol resin, bismaleimide resin, polyimide resin, cyanate resin, silicone rubber, fluororubber, butyl rubber, natural rubber, styrene-butadiene rubber, and chloroprene rubber; further, the polyolefin includes but is not limited to at least one of polyethylene, polypropylene, and polystyrene.
[0047] In the present invention, the ceramic forming temperature of the ceramic composition is not higher than 1000° C., and the ceramic forming time is not more than 45 minutes.
[0048] Compared with traditional ceramic polymers, the ceramic composition provided by the present invention has a low ceramic forming temperature and a short ceramic forming time, and can significantly improve the flame retardant effect and mechanical properties of the molded products prepared from the composition. Under preferred conditions, the ceramic forming temperature of the ceramic composition is 500-950°C, and the ceramic forming time is no more than 45 minutes.
[0049] In some preferred embodiments of the present invention, the porcelain-forming temperature of the porcelain-forming composition may be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any value in the range consisting of any two of the above numerical values; the porcelain-forming time of the porcelain-forming composition may be 2 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min or any value in the range consisting of any two of the above numerical values.
[0050] In the present invention, when the polymer resin is a thermoplastic resin, the ceramic composition can be blended and extruded, and the blending temperature can be 130-200° C.; when the polymer resin is a thermosetting resin, the ceramic composition can be blended and cured.
[0051] The present invention will be described in detail below through examples.
[0052] In the following examples, borax has a purity of 99.0%; zinc chloride has a purity of ≥98%;
[0053] The purity of tricalcium phosphate is ≥99%, and D50 is 4μm;
[0054] Calcium silicate purity ≥98%, D50 is 12μm.
[0055] The PE resin is a commercially available product of Borealis Model No. FB2230.
[0056] The EVA resin is a commercially available product of model ELVAX EVA260 from DuPont, USA.
[0057] Oxygen index test method: Determine the oxygen index of the molding material according to the method of national standard GB / T 24093.
[0058] Porcelain strength test:
[0059] 1) A sample with a length, width and height of 60 mm × 6 mm × 3 mm was kept in a muffle furnace at 950°C for 45 min; then the three-point bending strength was tested according to the method of GB / T 9341-2000.
[0060] 2) A sample with a length, width and height of 60 mm × 6 mm × 3 mm was continuously sprayed with a butane spray gun for 5 minutes; then the three-point bending strength was tested according to the method of GB / T 9341-2000.
[0061] The original tensile strength and elongation at break of the composite material were tested according to GB / T 1043.3-2006 method.
[0062] Example 1
[0063] 1) Dissolve 7.29 g of borax in 150 mL of water, disperse and stir evenly to form solution A;
[0064] Dissolve 15.63 g zinc chloride in 150 mL water and stir to form solution B.
[0065] Disperse and stir 40 g of tricalcium phosphate in 150 mL of water to obtain solution C;
[0066] 2) mixing solution B with solution C to obtain a mixed solution, and then adding a pH adjuster (0.5 mol / L sodium hydroxide solution) to adjust the pH to 8 to obtain a mixed solution D;
[0067] 3) adding solution A dropwise to mixed solution D to obtain mixed solution E, and then keeping mixed solution E at 90° C. for 6 h to obtain a crude product;
[0068] The crude product was cooled to room temperature, filtered, washed twice with deionized water, dried in a vacuum oven at 60°C, ground and sieved through a 150-mesh sieve to obtain zinc borate-coated tricalcium phosphate porcelain-forming powder.
[0069] 10 parts of PE resin, 40 parts of EVA resin, 0.05 parts of PE wax powder, 0.15 parts of antioxidant 168, 15 parts of low-melting-point glass powder and 35 parts of the ceramic powder prepared in Example 1 were weighed by mass and all were put into an internal mixer for blending. When the mixing temperature was raised to 160°C, the material was discharged after mixing for 15 minutes. After discharging, the material was processed by a flat vulcanizer at a processing temperature of 160°C, a processing time of 10 minutes and a pressure of 10 MPa to obtain a molding material.
[0070] The performance of the molding material prepared in Example 1 was tested, and the results are shown in Table 1.
[0071] Examples 2-4 and Comparative Example 1
[0072] The method of Example 1 is followed, except that different amounts of borax and zinc chloride are used, resulting in different ratios of zinc borate and tricalcium phosphate in the ceramic powder, as shown in Table 1.
[0073] The unexplained parts in Examples 2-4 and Comparative Example 1 are the same as those in Example 1.
[0074] The performance tests were performed on the molding materials prepared in Examples 2-4 and Comparative Example 1. The results are shown in Table 1.
[0075] Comparative Example 2
[0076] The method of Example 1 is followed, except that the same amount of tricalcium phosphate is used as the ceramic powder.
[0077] The unexplained parts in Comparative Example 2 are the same as those in Example 1.
[0078] The performance of the molding material prepared in Comparative Example 2 was tested, and the results are shown in Table 1.
[0079] Comparative Example 3
[0080] The method of Example 1 is followed, except that a physical mixture of zinc borate and tricalcium phosphate in the same amount is used as the porcelain-forming powder, as shown in Table 1.
[0081] The unexplained parts in Comparative Example 3 are the same as those in Example 1.
[0082] The performance of the molding material prepared in Comparative Example 3 was tested, and the results are shown in Table 1.
[0083] Table 1
[0084]
[0085]
[0086] It can be seen from Table 1 that the molding materials obtained in Examples 1-4 have a porcelain strength of more than 4.2 MPa after being kept at 950°C for 45 minutes. Under the condition of spraying with a butane spray gun for 5 minutes, the porcelain strength is as high as 3.5 MPa, and can reach a maximum of 5.5 MPa, which indicates that the molding materials prepared in the embodiments of the present invention have a low porcelain temperature and a short porcelain time.
[0087] It can be seen from Examples 1-4 and Comparative Example 1 that, under the condition that other conditions remain unchanged, when the mass ratio of zinc borate to tricalcium phosphate in the porcelain powder is (5-30):100, as the mass proportion of zinc borate continues to increase, the oxygen index and porcelain strength of the obtained molding material also gradually increase. However, when the mass ratio of zinc borate to tricalcium phosphate in the porcelain powder increases to 40:100, the oxygen index and porcelain strength of the molding material begin to decrease compared with Example 1.
[0088] By comparing Example 2 with Comparative Example 3, it can be seen that when the usage ratio of zinc borate to tricalcium phosphate is the same, compared with the physical mixing of zinc borate and tricalcium phosphate, the ceramic strength of the molding material can be significantly improved by chemically coating the zinc borate on the surface of tricalcium phosphate.
[0089] Figure 1 The SEM images of the ceramic powder prepared in Example 1 at different magnifications are shown; Figure 2 This is the SEM image of tricalcium phosphate in Comparative Example 2. Figure 1 and Figure 2 It can be seen that the surface of the ceramic powder of tricalcium phosphate coated with zinc borate is more uneven than that of the ceramic powder without coating;
[0090] pass Figure 3 It can be seen that the average size of the polymer added with the ceramic powder prepared in Comparative Example 3 after combustion is 58mm×6.2mm×5.8mm, and the average size of the polymer added with the ceramic powder prepared in Example 1 after combustion is 48mm×4.2mm×4.5mm. This indirectly indicates that after the polymer added with the ceramic powder prepared in Example 1 is burned, its interior is denser.
[0091] Example 5
[0092] The method of Example 1 is followed, except that tricalcium phosphate is replaced with the same amount of calcium silicate.
[0093] All parts not described in Example 5 are the same as those in Example 1.
[0094] The performance of the molding material prepared in Example 5 was tested, and the results are shown in Table 2.
[0095] Examples 6-8 and Comparative Example 4
[0096] The method of Example 5 is followed, except that different amounts of borax and zinc chloride are used, resulting in different ratios of zinc borate to calcium silicate in the ceramic powder, as shown in Table 2.
[0097] The unexplained parts in Examples 6-8 and Comparative Example 4 are the same as those in Example 5.
[0098] The performance tests were performed on the molding materials prepared in Examples 6-8 and Comparative Example 4. The results are shown in Table 2.
[0099] Comparative Example 5
[0100] The method of Example 5 is followed, except that a physical mixture of zinc borate and calcium silicate in the same amount is used as the porcelain-forming powder, as shown in Table 2.
[0101] The unexplained parts in Comparative Example 5 are the same as those in Example 5.
[0102] The performance of the molding material prepared in Comparative Example 5 was tested, and the results are shown in Table 2.
[0103] Table 2
[0104]
[0105] It can be seen from Table 2 that the molding materials obtained in Examples 5-8 have a porcelain strength of more than 3.5 MPa after being kept at 950°C for 45 minutes. Under the condition of spraying with a butane spray gun for 5 minutes, the porcelain strength is as high as 3.2 MPa, and can reach a maximum of 4.5 MPa, which indicates that the molding materials prepared in the embodiments of the present invention have a low porcelain temperature and a short porcelain time.
[0106] By comparing Examples 5-8 with Comparative Example 4, when other conditions remain unchanged, when the weight ratio of zinc borate to calcium silicate in the porcelain powder is (5-30):100, as the mass proportion of zinc borate continues to increase, the oxygen index and porcelain strength of the obtained molding material also gradually increase. However, when the mass ratio of zinc borate to calcium silicate in the porcelain powder reaches 40:100, the oxygen index and porcelain strength of the molding material begin to decrease relative to Example 5.
[0107] Figure 4 The cross-sectional diagram of the samples of the ceramic polymers of Example 6 and Comparative Example 5 after calcination; Figure 4 It can be seen that compared with the polymer filled with ceramic powder formed by physical mixing (Comparative Example 5), the ceramic polymer added with the ceramic powder prepared in Example 6 is denser inside after calcination, thereby being able to improve the compressive strength of the material.
[0108] After the molding material obtained in Example 6 was kept at 500°C for 45 minutes, its porcelain strength was 2.3 MPa; after the molding material obtained in Example 6 was kept at 750°C for 45 minutes, its porcelain strength was 3.2 MPa, indicating that the porcelain powder provided by the present invention can be formed into porcelain at 500°C.
[0109] Example 9
[0110] The method of Example 6 is followed, except that the amount of the porcelain-forming powder used is different, as shown in Table 3.
[0111] All parts not described in Example 9 are the same as those in Example 6.
[0112] The performance of the molding material prepared in Example 9 was tested, and the results are shown in Table 3.
[0113] Example 10
[0114] The method of Example 6 is followed, except that the amount of the porcelain-forming powder used is different, as shown in Table 3.
[0115] All parts not described in Example 10 are the same as those in Example 6.
[0116] The performance of the molding material prepared in Example 10 was tested, and the results are shown in Table 3.
[0117] Table 3
[0118]
[0119] It can be seen from Table 3 that when other conditions remain unchanged, as the amount of ceramic powder increases, the content of calcium silicate in the system increases at the same time, the oxygen index and ceramic strength of the polymer continue to increase, but the elongation at break of the polymer continues to decrease, and the tensile strength first increases and then tends to stabilize. Therefore, although increasing the content of ceramic powder in the resin-based composite material will improve the flame retardant properties and ceramic strength of the composite material, it will affect the mechanical properties of the composite material to a certain extent, and the addition ratio of ceramic powder needs to be controlled.
[0120] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A ceramic composition comprising a polymer resin and a ceramic powder, characterized in that: The ceramic powder comprises an inorganic flame retardant powder and zinc borate coated on the surface of the inorganic flame retardant powder; The mass ratio of the zinc borate to the inorganic flame retardant powder is (10-40): 100; The inorganic flame retardant powder is selected from at least one of phosphate and silicate.
2. The ceramic composition according to claim 1, characterized in that The particle size of the ceramic powder is 1-100 μm.
3. The ceramic composition according to claim 1, characterized in that: The particle size of the inorganic flame retardant powder is 0.5-90 μm.
4. The ceramicizable composition according to claim 3, characterized in that: The particle size of the inorganic flame retardant powder is 3-60 μm.
5. The ceramic composition according to claim 1, characterized in that: The preparation method of the ceramic powder comprises: 1) dissolving a boron source in a first solvent to obtain a solution A; dissolving a zinc source in a second solvent to obtain a solution B; dispersing the inorganic flame retardant powder in a third solvent to obtain a solution C; 2) mixing the solution B with the solution C to obtain a mixed solution, and then adjusting the pH value of the mixed solution to obtain a mixed solution D; 3) adding the solution A dropwise into the mixed solution D and stirring evenly to obtain a mixed solution E, and then heating the mixed solution E to a certain temperature and keeping it warm for a period of time to obtain the ceramic powder.
6. The ceramicizable composition according to claim 5, characterized in that: The mass ratio of the boron source, the zinc source and the inorganic flame retardant powder is (0.5~3): (0.5~3): (10~30).
7. The ceramicizable composition according to claim 5, characterized in that: The inorganic flame retardant powder is selected from at least one of phosphate and silicate.
8. The ceramic composition according to claim 5, characterized in that: The boron source is selected from at least one of borax, potassium borate and boric acid.
9. The ceramicizable composition according to claim 5, characterized in that: The zinc source is selected from at least one of zinc chloride, zinc nitrate and zinc sulfate.
10. The ceramic composition according to claim 5, characterized in that: The first solvent, the second solvent and the third solvent are each independently selected from at least one of water and an organic solvent.
11. The ceramic composition according to claim 5, characterized in that: In step 2), the pH value of the mixed solution D is 7.5-10.
12. The ceramic composition according to claim 5, characterized in that: In step 3), the mixed solution E is kept at 90-150° C. for 6-10 hours.
13. The ceramic composition according to claim 1, characterized in that: The ceramic forming temperature of the ceramic composition is not higher than 1000° C. and the ceramic forming time is not more than 45 minutes.
14. The ceramicizable composition according to claim 13, characterized in that: The ceramic forming temperature of the ceramic composition is 500-950° C., and the ceramic forming time is no more than 45 minutes.
15. The ceramic composition according to claim 1, characterized in that: The amount of the ceramic-forming powder is 10-70wt% based on the total amount of the polymer resin.
16. The ceramicizable composition according to claim 15, characterized in that: The amount of the ceramic-forming powder is 20-60wt% based on the total amount of the polymer resin.
17. The ceramicizable composition according to any one of claims 1 to 16, characterized in that The polymer resin includes at least one of polyolefin, polyolefin elastomer, polyphenylene ether resin, polyamide resin, polycarbonate, epoxy resin, polyurethane, acrylic resin, polyacrylonitrile resin, polyvinyl alcohol resin, bismaleimide resin, polyimide resin, cyanate resin, silicone rubber, fluororubber, butyl rubber, natural rubber, styrene-butadiene rubber, and chloroprene rubber.
Citation Information
Patent Citations
Method for preparing core-shell synergistic magnesium zinc composite flame retardants
CN104861201A